The Efficiency of Seed Priming with Dead Sea Water for Improving Germination and Early Seedling Growth of Wheat (Triticum aestivum L.) under Salinity - Samih Mohammad Tamimi (Caraka Tani: Journal of Sustainable Agriculture, 2024)
Salinity is considered the most critical environmental factor which negatively affects the germination and growth of plants. In this study, the potential of using Dead Sea water (DS) as a seed priming agent for the mitigation of the adverse effects of salinity on seed germination and growth performance of wheat (Triticum aestivum L.) was investigated. Germination of wheat seeds primed with different doses of DS; 0%, 5%, 10%, 15%, and 20% were evaluated under different saline conditions (0, 100, 200, and 300 mM NaCl). High salinity (300 mM NaCl) remarkably inhibited germination attributes and reduced seedling length. However, seeds primed with DS exhibited improved germination parameters and seedling growth. Among the different DS concentrations used, the 10% DS priming achieved the highest increase in final germination percentage tolerance, germination index, relative germination salt tolerance, and seedling length. The increased tolerance to salinity was associated with improved water imbibition, α-amylase activity, antioxidant capacity and osmotic homeostasis correlated with high proline and soluble sugar levels. In addition, DS priming increased the membrane stability index, and reduced malondialdehyde content and K+ leakage besides lowering Na+/K+ ratio. Overall, priming with DS could be a promising strategy for minimizing the damaging effects of salinity in wheat.